Mentorship and well-being: Examining doctoral students' lived experiences in doctoral supervision context. Issue 1 (3rd October 2019) - Al Makhamreh, Maha; Stockley, Denise
Abstract : Purpose: The purpose of this paper is to examine how doctoral students experienced mentorship in their supervision context and how the mentorship they received impacted their well-being. Design/methodology/approach: An interpretive phenomenological methodology was selected to frame the research design. This research approach seeks to study the individual lived experience by exploring, describing and analyzing its meaning. Findings: The findings revealed three different quality levels of mentorship in this context authentic mentorship, average mentorship and below average/toxic mentorship. Doctoral students who enjoyed authentic mentorship experiences were more motivated and satisfied, students who reported average mentorships needed more attention and time from their supervisors, and students who had below average/toxic mentorships were stressed out and depleted. Research limitations/implications: A limitation of this study is the lack of generalizability owing to the small sample size typical in qualitative studies. Another limitation is that this research did not include students who quit their programs because of dysfunctional supervision experiences. Practical implications: Students and supervisors can use the findings to reflect on their beliefs and practices to evaluate and improve their performances. Also, authentic mentors can benefit from the findings to create a positive culture for all students to receive support. Finally, current supervisory policies can be reviewed in light of this paper's findings. Social implications: The findings show the nature of mentorship in an authoritative context, and how it can be toxic when power is misused. Originality/value: This study provides new knowledge in relation to the different types of mentorship experiences that exist in doctoral supervision, and how each type can influence students' well-being differently. Additionally, it reveals that doctoral students can graduate, even in the face of toxic mentorship, but at the expense of their well-being.